Electronic structure study of wide band gap magnetic semiconductor (La0.6Pr0.4)0.65Ca0.35MnO3 nanocrystals in paramagnetic and ferromagnetic phases - Dwivedi G.D.; Joshi A.G.; Kumar S.; Chou H.; Yang K.S.; Jhong D.J.; Chan W.L.; Ghosh A.K.; Chatterjee S. (My University, 2025)
X-ray circular magnetic dichroism (XMCD), X-ray photoemission spectroscopy (XPS), and ultraviolet photoemission spectroscopy (UPS) techniques were used to study the electronic structure of nanocrystalline (La0.6Pr0.4)0.65Ca0.35MnO3 near Fermi-level. XMCD results indicate that Mn3+ and Mn4+ spins are aligned parallel to each other at 20 K. The low M-H hysteresis curve measured at 5 K confirms ferromagnetic ordering in the (La0.6Pr0.4)0.65Ca0.35MnO3 system. The low temperature valence band XPS indicates that coupling between Mn3d and O2p is enhanced and the electronic states near Fermi-level have been suppressed below TC. The valence band UPS also confirms the suppression of electronic states near Fermi-level below Curie temperature. UPS near Fermi-edge shows that the electronic states are almost absent below 0.5 eV (at 300 K) and 1 eV (at 115 K). This absence clearly demonstrates the existence of a wide band-gap in the system since, for hole-doped semiconductors, the Fermi-level resides just above the valence band maximum. © 2016 Author(s).